A new species of Paropsisterna Motschulsky, 1860, a significant pest of plantation eucalypts in Tasmania and Ireland (Coleoptera: Chrysomelidae: Chrysomelinae) - Reid, Chris A. M.; de Little, David W. (Zootaxa, 2013)
A new species of chrysomeline leaf beetle, Paropsisterna selmani Reid & de Little, is described, including all larval in-stars. This species, native to Australia, is now a significant pest of Eucalyptus plantations in Australia and Ireland, and has been recorded in southern England. Its occurrence in the British Isles represents the first record of establishment of a eu-calypt feeding chrysomelid in Europe.